2003
DOI: 10.1556/aphysiol.90.2003.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of noscapine with the bradykinin mediation of the cough response

Abstract: Angiotensin Converting Enzyme Inhibitors (ACEI) like captopril and enalapril, can induce persistant cough in man. Noscapine, an antitussive alkaloid, can be used to suppress ACEI-induced cough. Some workers have suggested a role for bradykinin in precipitation of ACE-induced cough. Work carried out in our laboratory has shown noscapine to be a non-competitive inhibitor of bradykinin in guinea pig ileum. It is therefore possible that noscapine suppresses cough by blocking the effect of bradykinin receptor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…showed that FR190976 (a bradykinin agonist) similar to ACEI could potentiate cough reflexes. 10 The present study shows that noscapine, a bradykinin antagonist, could effectively suppress cough in patients treated with ACEI. 9 This further supports the involvement of bradykinin in ACEI-induced cough reflexes.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…showed that FR190976 (a bradykinin agonist) similar to ACEI could potentiate cough reflexes. 10 The present study shows that noscapine, a bradykinin antagonist, could effectively suppress cough in patients treated with ACEI. 9 This further supports the involvement of bradykinin in ACEI-induced cough reflexes.…”
Section: Discussionsupporting
confidence: 51%
“…The only important and approved clinical effect of noscapine is its antitussive activity 8 . The experimental work with guinea pigs has shown that noscapine is very effective as an antitussive agent, 10 especially when cough is caused by bradykinin agonist FR190997 or ACEI, which inhibit the degradation of bradykinin 11 . The present work was carried out to investigate the effectiveness of noscapine in mitigating the dry cough induced by ACEI therapy.…”
mentioning
confidence: 98%
“…In the treatment of cancers, noscapine appears to interfere with the functioning of microtubule and thus in division of cancer cells while in treatment of stroke patients, noscapine seems to block the bradykinine β-2 receptors which help in recovery from the disease. Early studies in the treatment of prostate cancer are very promising [21]. Scientists have found a noticeable decrease in mortality in patients treated with noscapine [22].…”
Section: Economic Importance Of Opium Poppy and Its Derivativesmentioning
confidence: 99%
“…Papaverine is used in the treatment of spasms of the gastrointestinal tract, bile ducts and ureter. It is also used as a cerebral and coronary vasodilator in subarachnoid hemorrhage (combined with balloon angioplasty) and coronary artery bypass surgery [21,[23][24][25]. Papaverine is also used as an erectile dysfunction drug alone or sometimes in combination with phentolamine [26,27].…”
Section: Economic Importance Of Opium Poppy and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation